SENSITIVITY OF THE AEROSOL BACKGROUND OF THE CCATT-BRAMS MODELLING SYSTEM IN THE SHORT-TERM FORECAST - Ferrada, Gonzalo Andrés Guajardo (2016)
The difference between two simulations with different initial conditions in the CCATT-BRAMS modelling system in downward shortwave radiation at surface and cloudiness was studied for the zone corresponding to the state of Rondonia, on September 1 and 2, 2010, month in which was observed the greatest amount of fire outbreaks in the Amazon region. The difference in the initial configuration of the model was settled in activating aerosol background option in one of the simulations and turning it off in the other. No major differences in the fields of both analyzed variables and not much dependence with the amount of particulate matter in the atmosphere were observed. This was proved by calculating the correlation between aerosols and the changes of the variables in both simulations, showing low values (~0.2) within 48 hours studied.